2011
DOI: 10.1021/jo200337v
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Tether-Mediated Approach to the Formal Total Synthesis of (−)-Salicylihalamides A and B

Abstract: A concise formal synthesis of the cytotoxic macrolides (-)-salicylihalamides A and B is reported. Key features of the synthetic strategy include a chemoselective hydroboration, highly regio- and diastereoselective methyl cuprate addition, Pd-catalyzed formate reduction, and an E-selective ring-closing metathesis to construct the 12-membered macrocycle subunit. Overall, two routes have been developed from a readily prepared bicyclic phosphate (4-steps), a 13-step route and a more efficient 9-step sequence relyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…While the use and study of temporary silicon-based tether systems in ring-closing metathesis (RCM) is well represented in the literature, ongoing efforts in our group have sought to exploit the inherent properties of phosphate triesters to develop tripodal P -tether systems for the generation of complex polyol-containing intermediates en route to the total synthesis of natural products. This work has led to the completion of a number of total and formal syntheses, including dolabelide C, salicylihalimide A (formal synthesis), (−)-tetrahydrolipstatin, (+)-strictifolione, and lyngbouilloside (core macrolactone) . In an effort to expand the scope of the method, in 2013, we completed a detailed study on the effects of ring size and stereochemical complexity on the successful formation of bicyclo[4.3.1]-, bicyclo[5.3.1]-, and bicyclo[7.3.1]­phosphates , via diastereoselective RCM (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…While the use and study of temporary silicon-based tether systems in ring-closing metathesis (RCM) is well represented in the literature, ongoing efforts in our group have sought to exploit the inherent properties of phosphate triesters to develop tripodal P -tether systems for the generation of complex polyol-containing intermediates en route to the total synthesis of natural products. This work has led to the completion of a number of total and formal syntheses, including dolabelide C, salicylihalimide A (formal synthesis), (−)-tetrahydrolipstatin, (+)-strictifolione, and lyngbouilloside (core macrolactone) . In an effort to expand the scope of the method, in 2013, we completed a detailed study on the effects of ring size and stereochemical complexity on the successful formation of bicyclo[4.3.1]-, bicyclo[5.3.1]-, and bicyclo[7.3.1]­phosphates , via diastereoselective RCM (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, our group has utilized phosphate triesters as temporary tethers to desymmetrize a number of 1,3- anti -diol-containing dienes via ring-closing metathesis (RCM). 9 Focused on the chemistry of the bicyclo[4.3.1]phosphate, 10 this method served as the cornerstone in the synthesis en route to several natural products, including dolabelide C, 11 salicylihalimide A (formal synthesis), 12 (−)-tetrahydrolipstatin, 13 (+)-strictifolione, 14 and lyngbouilloside. 15 In 2013, we reported 16 a detailed study of the effects of ring size and stereochemical complexity in the phosphate tether-mediated desymmetrization of C 2 -symmetric 1,3- anti diol dienes 17 via RCM reaction to form P -stereogenic 18 , 19 bicyclo[4.3.1]-, bicyclo[5.3.1]-, 20 and bicyclo[7.3.1]phosphates 21 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, metathesis strategies incorporating multivalent activation of phosphate triesters for use in diastereoselective differentiation of 1,3- anti diol subunits 4 have been developed for the total synthesis of tetrahydrolipstatin, 5 dolabelide C 6 and the formal total synthesis of salicylihalamides A and B. 7 During the synthesis of tetrahydrolipstatin and dolabelide C, it was demonstrated that a stepwise sequence of RCM, CM, and chemoselective hydrogenation could be incorporated into a one-pot procedure to further streamline the synthetic route, albeit in non optimal conditions. 5 Advantages of this one-pot, sequential method were many-fold, namely in terms of the reaction time, waste generation, and ease of purification.…”
mentioning
confidence: 99%
“…Interest in the development of phosphate-based methodologies has led us to investigate the potential of a phosphate tether to mediate a sequence of reactions cleanly, selectively, and in one pot. Previously, metathesis strategies incorporating multivalent activation of phosphate triesters for use in diastereoselective differentiation of 1,3- anti diol subunits have been developed for the total synthesis of tetrahydrolipstatin and dolabelide C and the formal total synthesis of salicylihalamides A and B . During the synthesis of tetrahydrolipstatin and dolabelide C, it was demonstrated that a stepwise sequence of RCM, CM, and chemoselective hydrogenation could be incorporated into a one-pot procedure to further streamline the synthetic route, albeit in nonoptimal conditions .…”
mentioning
confidence: 99%